Pengembangan Bahan Ajar Mata Kuliah Pengembangan Media Pembelajaran Menggunakan Macro Media Flash Professional 8 - Purwati, Heni; Nugroho, Aryo Andri; Ariyanto, Lilik; Tsalatsa, Ahmad Nashir (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2016)
The research objective is to produce a module by using a Macromedia Flash both content and presentation material, which is able to contribute comprehension of concept of students in the subject of development of instructional media. This refers to the development of research Thiagarajan there are four phases, definition (define), design (design), development (develop), and dissemination (dessiminate). The development phase of module of the 4-D (Four D Device) Thiagarajan Semmel and Semmel to design a module on the course development of instructional media. The process of developing this module starts from the stage of defining or analysis. The process of designing a module that was developed based on information obtained from the analysis phase of the open-ended, students, materials, tasks that support and then do the design stage or the design. And then the last stage is the stage of development. Development of modules on the course development of instructional media developed proven valid content with the results of assessment for an average of 85.5%. The results are based on votes of validator to provides good value and can be used with minimal revision.Â Keywords: development, module, macromedia flash